Fractal Image Compression Techniques - Nitu,; Kumar, Yogesh; Rishi, Rahul (International Journal of Computer Sciences and Engineering, 2019)
Digital image are used in several areas. Digital image includes large amount of data. So transmission of such large amount of data require large storage space. Hence to deal which such problems, image compression is used. Image compression is a technique in which redundant information of image is removed, such that only essential information remain. Image compression technique is also helpful in reduce storage size, transmission bandwidth and transmission time. This paper provides review and comparison of different image compression techniques like DCT ( Discrete Cosine Transform ) , DWT ( Discrete Wavelet Transform) and Hybrid (DCT and DWT) and Fractal Image compression by using Affine Transformation and Iterated function system ( FIS). Research finding of this paper helps to build new and more effective image compression technique.